Botanical Composition and Forage Identification in Buffalo Grazing Lands of Salo Sub-district, Kampar Regency - Maulina Novita; Dedi Ramdani; Rahmat Hidayat; Vebrita Sari (Journal of Engineering Science and Technology Management, 2026)
Water buffaloes (Bubalus bubalis) hold a strategic role in smallholder farming systems and rural food security. Natural pastures in Salo Sub-district, Kampar Regency, serve as the primary extensive feed source. However, native forage productivity frequently faces constraints due to low soil fertility and high grazing pressure. This study aims to identify the botanical species and analyze the composition of forage vegetation in buffalo grazing lands within Salo Sub-district using an exploratory descriptive survey method combined with a vegetation analysis approach. Based on field observations, the botanical composition of the forages is categorized into three main groups. The identified grass species include Axonopus compressus (tropical carpet grass), Paspalum conjugatum (carabao grass), and Cynodon dactylon (Bermuda grass). The identified weed species include Spermacoce latifolia, Melastoma malabathricum L., Ammannia baccifera L., and Asystasia gangetica, some of which are utilized flexibly by livestock as part of mixed forage